Digital Art Innovation and Cultural Revitalization of the Bargello Museum in the Context of Globalization (Journal of Global Arts Studies, 2024)
Background: As global digitalization continues to accelerate, museums are increasingly adopting digital technologies to enhance visitor experiences and expand cultural dissemination. Bargello Museum, as an important cultural institution in Florence, faces challenges in balancing traditional exhibition approaches with the increasingly diverse needs of contemporary audiences, making digital transformation essential for supporting broader international outreach. Objective: This study aims to explore how digital strategies—including immersive technologies, narrative-based exhibitions, multilingual support systems, and open digital platforms—can optimize visitor experiences and promote international cultural dissemination at the Bargello Museum. Method: Through case study analysis and literature review, the research evaluates the current situation and developmental potential of the museum. Drawing upon relevant practices from British Museum and Rijksmuseum, the study proposes strategies for digital innovation and cultural communication enhancement. Results: The findings indicate that digital technologies have significantly improved the innovation and interactivity of museum exhibitions, while narrative-based strategies strengthen emotional connections between audiences and cultural content, thereby enhancing cultural identity, visitor engagement, and cross-cultural communication value. Conclusion: The digital transformation of the Bargello Museum represents not only a technological upgrade but also a transformation in cultural dissemination strategies. Through the integration of immersive technologies, narrative approaches, multilingual services, and open digital platforms, the museum demonstrates strong innovation and adaptability, providing valuable insights for small and medium-sized cultural institutions in the digital era.
Keywords: Digital Transformation; Artistic Design; Cultural Dissemination; Museum Innovation